Etiology and Pathogenesis of West Nile Virus - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2025)
West Nile Virus of Flaviviridae family was isolated in 1973 in Uganda before a wide story of its diffusion in all the world. This paper has the purpose to uptodate its story since Italy Healthcare is still talking only to bite trasmission by fly and not at all the infected blood.